Gut Microbiota Disorder Contributes to the Production of IL-17A That Exerts Chemotaxis via Binding to IL-17RA in Endometriosis - Li Y; Zhou Z; Liang X; Ding J; He Y; Sun S; Cheng W; Ni Z; Yu C (Dove Medical Press, 2024)
Yangshuo Li,1,* Zhihao Zhou,1,2,* Xiaolan Liang,1,* Jie Ding,1 Yalun He,1 Shuai Sun,1 Wen Cheng,1 Zhexin Ni,1,3 Chaoqin Yu1 1Department of Traditional Chinese Gynecology, the First Affiliated Hospital of Naval Military Medical University (Changhai Hospital), Shanghai, People's Republic of China; 2Traditional Chinese Medicine Department, No. 929 Hospital, Naval Medical University, Shanghai, People's Republic of China; 3Department of Pharmaceutical Sciences, Beijing Institute of Radiation Medicine, Beijing, 100850, People's Republic of China*These authors contributed equally to this workCorrespondence: Zhexin Ni, Department of Pharmaceutical Sciences, Beijing Institute of Radiation Medicine, 27 Taiping Road, Beijing, 100850, People's Republic of China, Email nizxzg@163.com Chaoqin Yu, Department of Traditional Chinese Gynecology, the First Affiliated Hospital of Naval Military Medical University (Changhai Hospital), 168 Changhai Road, Shanghai, 200433, People's Republic of China, Email cqyu@smmu.edu.cnIntroduction: Endometriosis (EM) is a chronic estrogen-dependent condition characterized by the growth of endometrial-like tissue outside the uterus, posing a significant burden on reproductive-aged women. Previous research has shown a correlation between gut microbiota dysbiosis and interleukin-17A (IL-17A) in EM patients. IL-17A, a promising immunomodulatory molecule, exerts dual roles in human physiology, driving inflammatory diseases. However, the functions and origins of IL-17A in EM remain poorly characterized.Methods: Single-cell data analysis was employed to characterize IL-17A activity in EM lesions. Fecal microbiota transplantation was conducted to explore the impact of gut microbiota on EM. Gut microbiota and bile acid metabolism were assessed via 16S rRNA sequencing and targeted metabolomics. Th17 cell proportions were measured using flow cytometry.Results: High expression of IL-17 receptor A (IL-17RA) was observed in myeloid cell subpopulations within EM lesions and may be involved in the migration and recruitment of inflammatory cells in lesions. Elevated IL-17A levels were further validated in peritoneal and follicular fluids of EM patients. Dysregulated bile acid levels, particularly elevated chenodeoxycholic acid (CDCA) and ursodeoxycholic acid (UDCA), were found in the gut and peritoneal fluid of EM mouse models. Additional CDCA administration reduced EM lesions and modulated Th17 cell proportions, while UDCA showed no significant effects.Discussion: Our findings shed light on the origins and functions of IL-17A in EM, implicating its involvement in lesion migration and recruitment. Dysregulated bile acid metabolism may contribute to EM pathogenesis, with CDCA exhibiting therapeutic potential. Keywords: endometriosis, single-cell sequencing, interleukin-17, gut microbiota, bile acids, myeloid cell